Leiomyoma of the bladder. Apropos of a case and review of the literature - Goldberg, J. [UNESP]; Amaro, J. L.; Vercesi, L.; Trindade, J. C. (My University, 1994)
Mesodermal tumors of the urinary tract are unusual, being leiomyoma the most frequent tumor type. We present a case of leiomyoma of the urinary bladder in a 29 year old woman and review the literature. Clinical features, diagnosis and treatment are discussed.